Successful simultaneous laparoscopic repair of concurrent diaphragmatic eventration, hiatal hernia, and recurrent inguinal hernia in a single procedure: a case report - Gao, Chenjie; Pu, Yansong; Song, Bin (Frontiers in Surgery, 2026)
This article presents the case of a 59-year-old female patient with left-sided diaphragmatic eventration, hiatal hernia, and recurrent left inguinal hernia. A carefully planned single laparoscopic procedure was developed to carry out partial diaphragmatic resection with mesh reinforcement, hiatal hernia repair with Nissen fundoplication, and tension-free inguinal hernia repair, all based on detailed preoperative imaging evaluation. The innovative aspects of this procedure include: (1) a simultaneous transabdominal approach for the management of diaphragmatic eventration and multiple hernias; (2) the use of a linear stapler for partial diaphragmatic resection to reduce suture tension; and (3) reinforcement of the weakened diaphragmatic area with a double-layer mesh. The patient recovered well postoperatively without complications. The goal of this example is to give a new view of the minimally invasive care of complicated multiple hernias.